The inimitable Qurʾān : some problems in English translations of the Qurʾān with reference to rhetorical features - Blankinship, Khalid Yahya, (Women Writers in History;, 2020)
In The Inimitable Qurʾān: Some Problems in English Translations of the Qurʾān with Reference to Rhetorical Features, Khalid Yahya Blankinship examines certain Arabic rhetorical features of the Qurʾān as represented in seven English translations. The author addresses the intersection of two important topics in Qurʾānic studies: the critique of the available English translations and the role of rhetoric in the interpretation of the Qurʾān. He identifies a number of figures characteristic of Qurʾanic style which represent some of the chief stumbling blocks for readers who are used to English in attempting to understand, interpret, and appreciate the text. The book should be useful to all those interested in rhetorical and translation studies and theory as well as Islamic studies.